Aerobic Exercise Training Exerts Beneficial Effects Upon Oxidative Metabolism and Non-Enzymatic Antioxidant Defense in the Liver of Leptin Deficiency Mice - Fernandes, Matheus Santos de Sousa; Silva, Lucas de Lucena de Simões e; Kubrusly, Márcia Saldanha; Lima, Talitta Ricarlly Lopes de Arruda; Muller, Cynthia Rodrigues; Américo, Anna Laura Viacava; Fernandes, Mariana Pinheiro; Cogliati, Bruno; Stefano, José Tadeu; Lagranha, Claudia Jacques; Evangelista, Fabiana S.; Oliveira, Claudia P. (Frontiers in Endocrinology, 2020)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common forms of liver disease, which is associated with several etiological factors, including stress and dysfunction in oxidative metabolism. However, studies showed that aerobic exercise training (AET) can combat the oxidative stress (OS) and improves mitochondrial functionality in the NAFLD. To test the hypothesis that AET improves oxidative metabolism and antioxidant defense in the liver of ob/ob mice. Male ob/ob mice with eight weeks old were separated into two groups: the sedentary group (S), n=7, and the trained group (T), n=7. The T mice were submitted to an 8-week protocol of AET at 60% of the maximum velocity achieved in the running capacity test. Before AET, no difference was observed in running test between the groups (S=10.4 ± 0.7 min vs. T= 13 ± 0.47 min). However, after AET, the running capacity was increased in the T group (12.8 ± 0.87 min) compared to the S group (7.2±0.63 min). In skeletal muscle, the T group (26.91±1.12 U/mg of protein) showed higher citrate synthase activity compared with the S group (19.28±0.88 U/mg of protein) (p =0.006). In the analysis of BW evolution, significant reductions were seen in the T group as of the fourth week when compared to the S group. In addition, food intake was not significant different between the groups. Significant increases were observed in the activity of enzymes citrate synthase (p=0.004) and β-HAD (p=0.01) as well as in PGC-1a gene expression (p=0.002) in the liver of T group. The levels of TBARs and carbonyls, as well as SOD, CAT and GST were not different between the groups. However, in the nonenzymatic antioxidant system, we found that the T group had higher sulfhydryl (p = 0.02), GSH (p=0.001) and GSH/GSSG (p=0.02) activity. In conclusion, the AET improved body weight evolution and the aerobic capacity, increased the response of oxidative metabolism markers in the liver such as PGC-1a gene expression and citrate synthase and β-HAD enzyme activities in ob/ob mice. In addition, AET improved the non-enzymatic antioxidant defense and did not change the enzymatic defense.